Kennedy Urges Cigarette Curbs, Will Offer Senate Bills To Extend Advertising Rules And Establish Tax Scale, Makers Are Assailed, Senator Scores Companies Regulation-Industry Says It Meets Responsibility (Tufts Archival Research Center, 2007)
Article written in 1967 reporting on Senator Robert Kennedy's opposition of tobacco companies. Quotes the Senator as saying that were it not for the tremendous power of tobacco companies, cigarettes would have been outlawed years ago. Includes a response from the Tobacco Institute contradicting Senator Kennedy's findings that the tobacco industry does not have any self regulation. Insists that they do everything they can to follow government regulations.